Conflictos territoriales asociados a la expansión de la ciudad entre 2014 y 2023 en la vereda Quiba, Ciudad Bolívar, Bogotá D.C. - Marín Guerrero, Nini Johanna (Universidad Pedagógica y Tecnológica de Colombia., 2024)
Eng: When we talk about the peri-urban, we often tend to generalize in terms of the social, environmental characteristics and their problems, however, what can be concluded is precisely that particularity that these spaces have, and the need that arises to study them, analyze them, to improve the understanding of their dynamics and, therefore, to be able to contribute to the improvement of the quality of life of these communities that inhabit it. In this sense, this research was carried out, which delves into the southern peri-urban area of the City, vereda Quiba, in order to understand and analyze the territorial conflicts raised in almost a decade of growth of the city (2014-2023). Territorial conflicts associated with water, land use and land tenure were identified, all related to urban expansion and investigated through tools such as semi-structured interviews, tours, and participatory cartography.